2011
DOI: 10.1542/peds.2010-3373
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Observation on Cranial Computed Tomography Utilization for Children After Blunt Head Trauma

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Emergency-department observation of children with minor blunt head trauma for symptom progression before making a decision regarding computed tomography may decrease computed tomography use. The actual impact of this strategy on computed tomography use and clinical outcomes, however, is unknown. WHAT THIS STUDY ADDS:Clinicians currently observe some children with head trauma before deciding whether to obtain a cranial computed tomography scan. Patients who were observed had a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 22 publications
1
72
0
5
Order By: Relevance
“…A similar approach to the utilization of head CT among blunt injured children has led to a decrease in CT use. 14 We found that a similar decrease in abdominal CT utilization may be achieved with our criteria that stratifies patients into low risk and at-risk groups.…”
Section: Discussionsupporting
confidence: 59%
“…A similar approach to the utilization of head CT among blunt injured children has led to a decrease in CT use. 14 We found that a similar decrease in abdominal CT utilization may be achieved with our criteria that stratifies patients into low risk and at-risk groups.…”
Section: Discussionsupporting
confidence: 59%
“…For children with mild TBI (GCS scores of 14 and 15), clinical observation before making a decision to obtain NCCT is therefore an effective strategy in reducing unnecessary radiation exposure for young children (class IIa recommendation). Additional studies will be necessary to determine the optimal duration of clinical observation to measure the impact on CT utilization, the total length of the ED stay, as well as the overall costs [133].…”
Section: Which Pediatric Patients With Tbi Can Safely Avoidmentioning
confidence: 99%
“…1,5,13 These guidelines are useful for assessing the different levels of risk in children with MHT, leading to a reduction in the rate of CT use. 14 Of these guidelines, the one developed based on the largest cohort of patients was that of the Pediatric Emergency Care Applied Research Network (PECARN), which is considered the most valid for infants as well as older children. 1,15 While none of the international clinical guidelines recommends the use of skull radiography to assess patients with MHT, this test is often used in emergency departments and several authors support its use for the detection of skull fractures, as the presence of a skull fracture in an infant is a risk factor for traumatic brain injury, and possibly the most relevant following changes in the level of consciousness.…”
Section: Introduction and Objectivesmentioning
confidence: 99%